The Influence Work Discipline on Community Satisfaction at the East Luwu Regency Social Service Office - Riska, Riska; Nasrullah, Muh.; Nasir, Nasir; Suprianto, Suprianto (ASHA Publishing, 2024)
Community satisfaction is one of the most important variables in determining the result of a service. Therefore, the implementation of employee discipline must be implemented so that employee performance can be more optimal. The purpose of this study is to determine the influence of employee work discipline on community satisfaction at the East Luwu Regency Social Service office. This research is classified as bivariate research with a quantitative approach. The sample in this study amounted to 96 people from East Luwu Regency using probability sampling techniques. In this study, the data collection techniques used are questionnaires, observations and documentation. The data analysis techniques used in this study are descriptive statistical analysis and inferential statistical analysis. The results of the study show that the variables of employee work discipline at the East Luwu Regency Social Service Office are in the good category with indicators, namely time discipline, regulatory discipline, and responsibility discipline, while the variables of community satisfaction are in the good category with indicators, namely the suitability of expectations, performance perception, and community assessment. Based on the results of the product moment correlation test, the relationship between variables is strong. Based on the results of a simple linear regression analysis, it was concluded that there was a positive and significant influence between employee work discipline and community satisfaction at the East Luwu Regency Social Service Office